Growing Trend in Edible Oil Consumption-An Analysis - S. Suchithra Devi (RESEARCH ESSENCE, 2013)
India is the largest producer of oilseeds in the world and the oilseed sector occupies an important Position in the country’s economy. The country accounts for 12- 15 percent of global oilseeds area, 6-7 percent of vegetable oils production and 9-10 percent of the total edible oil consumption. In terms of acreage, production and economic value, oilseeds are second only to food grains. Among different oilseeds ground nut, rapeseed- mustard and soya bean account for about 80 percent of area and 87percent of production of oilseeds in the country (2010-2011).The domestic demand for vegetable oils and fats has been rising rapidly, at a rate of 6 percent per annum, but our domestic output has been increasing at just about 2 % per annum. There has been a large gap between domestic demand and production. Thus the countries meet half of its edible requirement through import, which act as a significant drain on foreign exchange reserves of the country. It increased from 4.9 Mt in 2007-08 to 8.1 Mt in 2009-10.The increase in demand of edible oil is due to different contributing factors like rising income, growing population and expanding urbanization. The present scenario calls for some urgent measures to be taken to set up oilseeds production on a sustainable basis to keep pace with their increasing demand. The present study attempts to analyze the production and consumption of edible oil both under global and Indian scenario. The increasing trend in imports over years has also been analyzed. The NSSO data available from various rounds has been used to examine the trend in consumption expenditure of edible oil at the household level.